Betatrophin is correlated with glucagon and insulin release rather than insulin resistance marker in type 2 diabetes mellitus Iraqi women - Mohammed, Athir K.; Khazaal, Faris A. K. (International Journal of Research in Medical Sciences, 2016)
Background: Betatrophin mainly expressed in liver and adipose tissue, stimulates pancreatic β-cell proliferation in insulin resistance state and improves metabolic process‎ regulation. This study aimed to understand effective roles of betatrophin in diabetic and non-diabetic Iraqi women. Also, it’s correlation with some insulin markers, metabolic parameters and glucagon. Methods: Eighty women participated in this cross-sectional study, (mean body mass index: 21 - 49 kg/m2; mean age: 25-50 years) were enrolled and classified according to the presence of diabetes into 2 groups (40 diabetic and 40 non-diabetic). Anthropometric, biochemical and metabolic parameters measured. Results: Betatrophin level had no statistically significant differences between non-diabetics and diabetics. Serum betatrophin levels had no statistically significant positive or negative correlations with age, anthropometric, lipid profile, diabetic parameters, thyroid stimulating hormone, glucagon, irisin, glucagon like peptide -1 and hepatocyte growth factor except uric acid (r=0.2539, P =0.0231). Serum betatrophin had no statistically significant correlations with all variables in non-diabetic and diabetic groups except with homoeostasis model assessment- for β-cell function (HOMA-β) and glucagon (r=0.3647, P=0.0207; r=0.3403, P=0.0317 respectively) in the diabetic group. Stepwise regression showed that only uric acid was independently related factors to circulating betatrophin β=‎0.8500, P=‎0.02. Conclusions: Betatrophin was positively correlated with HOMA-β and glucagon in type 2 diabetes mellitus women. Uric acid was a direct independent predictor of betatrophin level.